Behaviour of soft soils following soil mixing in controlled and uncontrolled environments. Issue 3 (27th August 2022) - Sivakumar, Vinayagamoothy; Walker, Sian; Ewart, Adam; Doherty, Ciaran; Donohue, Shane
Abstract : Soil mixing is considered to be effective for a range of applications and the required design specifications can be achieved by varying the percentage of additives, commonly cement and lime. This paper describes the results of a comprehensive laboratory investigation involving the assessment of cement/lime treatments for improving the geotechnical characteristics of three different soft clays: kaolin, sleech and Belfast clay. The investigation is coupled with an assessment of the durability of the treated soil and the effects of water ingress after treatment. Observations showed that the large-strain Young's modulus increased significantly with curing period after 28 days. The evolution of the small-strain shear stiffness was progressive, and all soils exhibited a steady increase in stiffness, the rate of which reduced as the curing period approached 7 days. The relative increase in strength of the different soils was highly variable. It is postulated that suction was one of the contributors to undrained shear strength gain. When allowed access to water, strength and stiffness increased, although at a much reduced rate. The stress–strain behaviour of kaolin also changed from ductile when untreated to highly brittle as the curing period approached 90 days.